2019
DOI: 10.1136/bmjopen-2019-033933
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences of people in Ontario, Canada who have trouble affording medicines: a qualitative concept mapping study

Abstract: ObjectivesThe experiences of people who report cost-related medicine non-adherence are not well documented. We aimed to present experiences relating to accessing medicines reported by the participants in a randomised controlled trial of free medicine distribution.MethodsThe trial consisted of primary care patients from a large urban family practice and three rural family practices who reported cost-related medicine non-adherence. Participants were randomly allocated to continue their poor access (control) or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…A 2019 qualitative concept mapping study in Canada reported that those with access to free medicine had reduced stress, better communication with physicians, improved quality of life and a decreased need to sacrifice other essential items for health and well-being. 41 It is possible that OHIP+ had a positive effect on other important patient-reported outcome measures such as diabetes distress, diabetes-related quality of life and those described in this mapping study.…”
Section: Ohip+mentioning
confidence: 89%
“…A 2019 qualitative concept mapping study in Canada reported that those with access to free medicine had reduced stress, better communication with physicians, improved quality of life and a decreased need to sacrifice other essential items for health and well-being. 41 It is possible that OHIP+ had a positive effect on other important patient-reported outcome measures such as diabetes distress, diabetes-related quality of life and those described in this mapping study.…”
Section: Ohip+mentioning
confidence: 89%
“… 60 This continuous and cyclical relationship can have a negative impact on women’s ability to access health professionals that are not covered by provincial health insurance programs or medications or other therapies that may support optimal health. Findings from Yaphe et al’s 61 qualitative study revealed the financial burden of accessing medications and called for policies that support universal, government funded pharmacare programs in order to reduce this burden. Pharmacare programs could help women with episodic disabilities by reducing the burden of medication costs; however, more research is needed to understand the benefits of pharmacare for women with episodic disabilities and chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…As per concept mapping methods, data from the statement sorting and the ratings of importance/changeability were then analyzed using the free, open‐source software R‐CMap, as described by Bar and Mentch, 41 and used in other health‐related publications 42,43 . The first analysis step involved multidimensional scaling which produces a two‐dimensional visualization plot illustrating how participants judged similarity between the generated statements 41,44 .…”
Section: Methodsmentioning
confidence: 99%
“…As per concept mapping methods, data from the statement sorting and the ratings of importance/changeability were then analyzed using the free, open-source software R-CMap, as described by Bar and Mentch, 41 and used in other health-related publications. 42,43 The first analysis step involved multidimensional scaling which produces a two-dimensional visualization plot illustrating how participants judged similarity between the generated statements. 41,44 For example, statement 49 from the tertiary facility "Local services require upskilling to provide ongoing management and care" and statement 10 "We need to offer education/training and support for our rural/ community clinicians for them to feel confident at providing follow up care for HNC patients" were frequently sorted into similar piles indicating a high level of agreement between staff, and hence these two statements appear close together on the plot.…”
Section: Stage 4-representation and Stage 5-interpretation Stagesmentioning
confidence: 99%